(untitled) (Stamford Journal of Microbiology, 2023)
In the era of science and modern technology, environmental pollution is still the threat to survival of mankind. With the increasing urbanization process, anthropogenic sources of toxic heavy metals like mercury, lead, arsenic, chromium are also rising rapidly. Inadequate measures have been taken to mitigate the detrimental effects of such pollution. Among many mitigations process like physical, chemical and biological methods; microbial remediation is eco-friendly and cost-effective process and converts the toxic substances to the least toxic forms. By the blessing of modern science, various advanced molecular techniques (i.e. genetically modified organisms) can also be utilized. This review article summarizes the mitigation techniques of toxic heavy metals with emphasis to microbial remediation. However, more research is required to make them more expedient for mass use. Above all the remedies, cognition and circumspection are the exigent demands. Stamford Journal of Microbiology, 2023. Vol. 13, Issue 1, p. 42-51